THE EFFECT OF TRUST AND SERVICE CONVENIENCE ON BEHAVIORAL INTENTION TO UTILIZE ONLINE SERVICES OF AMIL ZAKAT INSTITUTION - Muhammad Syifa; Ririn Tri Ratnasari (Universitas Airlangga, 2020)
ABSTRAKDalam era digital seperti sekarang ini teknologi berkembang sangat pesat, jumlah dari pengguna layanan online pun setiap tahun terus berkembang tak terkecuali pun Lembaga Amil Zakat terus berinovasi agar tetap survive di era digital seperti sekarang ini. Peneliti ingin menjelaskan serta menggambarkan apakah faktor yang mempengaruhi melalui trust dan service convenience terhadap behavioral intention to utilize layanan online Lembaga Amil Zakat yang disebarkan melalui kuesioner online dengan karakteristik responden beragama islam, laki-laki dan perempuan berumur 18 tahun keatas, dan pernah memanfaatkan layanan online Lembaga Amil Zakat. Berdasarkan data yang didapat penulis mendapatkan 184 responden, tetapi diantara 184 responden tersebut peneliti hanya menggunakan 100 responden karena 84 responden lain tidak valid. Metode analisis yang digunakan yaitu menggunakan Structural Equation Model (SEM) dan Partial Least Square (PLS).Kata Kunci: Service Convenience, Trust, Behavioral Intention to Utilize ABSTRACTIn the digital era as now, technology is developing very rapidly, the number of online service users continues to grow every year, even though the Amil Zakat Institute continues to innovate in order to continue to survive in the digital era as it is today. The researcher wants to explain and illustrate whether the factors that influence through trust and service convenience towards behavioral intention to utilize online services of the Amil Zakat Institution are distributed through online questionnaires with the characteristics of Muslim respondents, men and women aged 18 years and over, and have used online services. Amil Zakat Institution. Based on the data obtained by the author to get 184 respondents, but among these 184 respondents, researchers only used 100 respondents because 84 other respondents were invalid. The analytical method used is the Structural Equation Model (SEM) and Partial Least Square (PLS).Keywords: Service Convenience, Trust, Behavioral Intentions to Utilize